5.2.4 Rechenregeln für Grenzwerte
lim
x
→
x
0
C
·
f
(
x
) =
C
· lim
x
→
x
0
f
(
x
)
, wobei
C
= konstant.
lim
x
→
x
0
f
(
x
) ±
g
(
x
) = lim
x
→
x
0
f
(
x
) ± lim
x
→
x
0
g
(
x
)
lim
x
→
x
0
f
(
x
) ·
g
(
x
) = lim
x
→
x
0
f
(
x
) · lim
x
→
x
0
g
(
x
)
lim
x
→
x
0
(
f
(
x
))
1/
n
= (lim
x
→
x
0
f
(
x
))
1/
n
lim
x
→
x
0
(
f
(
x
))
n
= (lim
x
→
x
0
f
(
x
))
n
lim
x
→
x
0
a
f
(
x
)
=
a
lim
x
→
x
0
f
(
x
)
lim
x
→
x
0
log
a
(
f
(
x
)) = log
a
(lim
x
→
x
0
f
(
x
))
Beispiel 5 - 8:
lim
x
→ 0
(
x
2
−2
x
+5)/cos
x
=
lim
x
→ 0
(
x
2
−2
x
+5)/lim
x
→ 0
(cos
x
)
=
5/1